Evaluasi Jumlah Leukosit, Jumlah Netrofil, dan Kadar Anti Streptolysin O pada Pasien Tonsilitis Anak - Citra Nadia Salsabila; Dita Pratiwi Kusuma Wardani; Arif Mulyanto; Defi Nurul Hayati (Jurnal Biodiversitas dan Bioteknologi, 2025)
Tonsillitis is a common global disease that most frequently affects children, particularly those aged 5–9 years. The primary cause of tonsillitis is infection of the tonsils by Streptococcus ?-hemolyticus Group A bacteria. Leukocytes play a key role in fighting infections, while neutrophils, as the main cells involved in acute inflammation, destroy bacteria through phagocytosis. This study aimed to determine the correlation between leukocyte and neutrophil counts and Anti-Streptolysin O (ASO) levels in children with tonsillitis. This research employed a cross-sectional design involving 32 pediatric tonsillitis patients, both inpatients and outpatients, at Dr. R. Goeteng Taroenadibrata Regional Hospital, Purbalingga. ASO levels were measured using the latex agglutination method, while hematological parameters—total leukocyte and neutrophil counts—were measured using a hematology analyzer based on the flow cytometry method. Data on the correlation between leukocyte and neutrophil counts and ASO levels were analyzed using Spearman’s rho correlation test. The results showed no significant correlation between leukocyte count and ASO level (p = 0.424, r = 0.146), and no correlation between neutrophil count and ASO level (p = 0.653, r = 0.083). There was no significant correlation between leukocyte and neutrophil counts and ASO levels in children with tonsillitis. Further studies are recommended using ASO measurement methods such as ELISA or turbidimetry, as well as additional inflammatory markers including Interleukin-1 (IL-1), Interferon-? (IFN-?), and Tumor Necrosis Factor-? (TNF-?).